2018
DOI: 10.13080/z-a.2018.105.013
|View full text |Cite
|
Sign up to set email alerts
|

Mineral nitrogen in soils of Lithuania’s agricultural land: comparison of oven-dried and field-moist samples

Abstract: Please use the following format when citing the article: Arbačauskas J., Masevičienė A., Žičkienė L., Staugaitis G. 2018. Mineral nitrogen in soils of Lithuania's agricultural land: comparison of oven-dried and field-moist samples. Zemdirbyste-Agriculture, 105 (2): 99- AbstractMineral nitrogen (N min = N-NH 4 + + N-NO 3 − ) in oven-dried and field-moist samples was investigated in 2011-2014 in five areas of Lithuania with soils of different texture (sand, sandy loam, loam and clay) and different mineral nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…In contrast to our findings, Sądej and Przekwas [ 59 ] revealed that ammonium dominated over nitrate in soils. Similar results were presented by Arbačauskas et al [ 56 ] who documented that concentrations of nitrate also have a decreasing tendency through depth. Similar tendencies were also presented in our study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast to our findings, Sądej and Przekwas [ 59 ] revealed that ammonium dominated over nitrate in soils. Similar results were presented by Arbačauskas et al [ 56 ] who documented that concentrations of nitrate also have a decreasing tendency through depth. Similar tendencies were also presented in our study.…”
Section: Discussionsupporting
confidence: 90%
“…It can be stated that for agricultural sites presented in this study, the concentrations of ammonium were lower than the average concentrations measured for Polish agricultural soils. According to Lee et al [ 54 ], the median concentration of ammonium in agricultural soils was equal to 4 mg kg −1 , whereas in Lithuanian agricultural lands, concentrations of ammonium were observed at the level of 1 mg kg −1 at the depth of 0.00–0.30 m; 0.84 mg kg −1 at the depth of 0.30–0.60 m; and 0.84 mg kg −1 at the depth of 0.60–0.90 m. Nitrate concentrations measured in Lithuanian soils were equal to 6.45 mg kg −1 at the depth of 0.00–0.30 m; 4.19 mg kg −1 at the depth of 0.30–0.60 m, and 2.86 mg kg −1 at the depth of 0.60–0.90 m [ 56 ]. For comparison, Długosz and Piotrowska-Długosz [ 57 ] revealed that the average concentrations of the total N, nitrate, and ammonium in the soils of northwestern Poland were 1.99 g kg −1 , 17.1 mg kg −1 and 11.1 mg kg −1 , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In each plot, the soil sample (300-400 g) consisted of four to five sub-samples, taken at randomly selected places. Mineral nitrogen (N min ) was measured via a spectrometric method as described by Arbačauskas et al (2018).…”
Section: Methodsmentioning
confidence: 99%
“…Considering soil texture, N min scales of assessment in mineral soils are developed (Staugaitis et al, 2007;Arbačiauskas et al, 2014). Optimal terms of soil sampling for N min analyses are determined in different countries according to climatic conditions, the depths from which samples are taken for different agricultural crops and other methodological requirements Zhang et al, 2015;Arbačauskas et al, 2018). Most of these studies are conducted early in spring and autumn, less often in summer, as due to intense mineralisation of plant residues and organic matter in the soil, the content of N min significantly increases (Aurangojeb et al, 2017;Friesen, Cattani, 2017;Tripolskaja et al, 2017).…”
Section: Introductionmentioning
confidence: 99%